THE INFLUENCE OF CULTURE ON THE JAPANESE LANGUAGE (World Bulletin of Social Sciences, 2024)
This work analyses an actual aspect of the influence of culture on the Japanese language, the impact of Chinese writings to Japanese language. Besides, the article researches the reflection of Japanese culture in Japanese lexicography. Researchers of culture do not always take into account such an important component as language. It is often believed that language is just a shell in which certain thoughts and ideas are contained, and for a cultural scientist it is an auxiliary means for understanding culture. But almost two centuries ago, the great thinker Wilhelm von Humboldt wrote: “Language is closely intertwined with the spiritual development of mankind and accompanies it at every stage of its local progress or regression, reflecting every stage of culture”. In the 20 th century such prominent scientists as E. Sapir and N.S. wrote about language as the most important component of culture. Japanese scientists also point out this. Besides, the primary component of the culture of every nation is linguistic culture, which includes the use of language in certain spheres of life by certain people, peculiarities of views on language, linguistic pictures of the world, etc. Now this issue is being actively studied in science in different countries, including Uzbekistan.
Keywords: “Manyoshu”; hieroglyph; “nihonjinron”; harmony